Jumping and swimming performance of burbot and white sucker: implications for barrier design - Gardunio, Eric, author; Myrick, Christopher, advisor; Bestgen, Kevin, committee member; Hooten, Mevin, committee member; Bledsoe, Brian, committee member; Zafft, David, committee member (Colorado State University. Libraries, 2014)
Chapter 1 - Illegally introduced burbot (Lota lota) populations have spread throughout the Green River drainage (GRD) of the upper Colorado River Basin in Wyoming and Utah, USA where they are having adverse effects on native and sport fisheries. We analyzed existing data to evaluate the status of burbot in southwestern Wyoming. Burbot appear to have been illegally introduced into Big Sandy Reservoir in the early- to mid-1990's, based on capture of burbot in 2003 that included one 16 year old fish and several between 7 and 12 years of age. Burbot began expanding throughout the Green River Drainage in the early 2000s and, with the assistance of a secondary introduction into Fontenelle Reservoir, have successfully invaded most portions of the GRD upstream of the Flaming Gorge Dam. Only one burbot has been captured downstream of Flaming Gorge Reservoir, but this detection indicates potential for downstream establishment in the future. Burbot are difficult to sample, especially in large rivers, so we recommend sampling techniques to monitor the expansion of burbot in lotic and lentic habitats of the upper Colorado River Basin as well as highlight research opportunities associated with this invasion. Chapter 2 - Burbot (Lota lota L.) and white suckers (Catostomus commersonii L.) are managed as invasive species in the upper Colorado River Basin and physical barriers to their upstream dispersal could be important tools for preventing their spread. A three-tiered lab-based experimental approach was used to define design parameters for both species utilizing a hybrid barrier that combines a vertical drop with a downstream velocity segment. The first tier of the study measured fish jumping ability over a range of waterfall height × plunge pool depth treatments to refine waterfall design parameters. Jumping attempt and waterfall exploration data were collected in each trial to allow a novel approach for examining the behavior associated with individual motivation to ascend the barrier, and to confirm that all height × depth treatments were challenged. The second tier of the study used constant acceleration trials (CATs) to define the length-specific burst transition (Bt) from aerobic (high-endurance; sustained) to anaerobic (rapid-fatigue; burst) swimming. Finally, the third tier of the study used fixed velocity trials at velocities > Bt to collect anaerobic endurance data that were used to solve Peake's equation to identify velocity × barrier length combinations that prevented upstream passage. To account for peak-performing individuals, upper 99% prediction intervals were used to determine design criteria that would prevent passage of fish of the total length (TL) in their system of interest. Minimum waterfall heights > 85% and 100% of the TL of the largest white sucker and burbot, respectively, in the system were found to prevent passage. Coupling these heights with plunge pools < 40% and 30% of white sucker and burbot TL increases the difficulty these species have ascending the fall. The CATs indicated that velocity barriers that deliver minimum velocities of 4.0 and 3.2 times the TL of the largest white sucker and burbot, respectively, in the system will ensure anaerobic swimming and thus fatigue fish prior to leaping attempts. A variety of velocity barrier length × velocity design parameters are defined for each species to prevent passage based on the FVTs and Peake's equation analysis.
Keywords: invasion; passage; endurance; gait transition; leaping